1994
DOI: 10.1271/bbb.58.1745
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression ofPseudomonas putidaEsterase Gene inEscherichia coliand Its Use in Enzymatic Production ofd-β-Acetylthioisobutyric Acid

Abstract: The esterase catalyzes the stereoselective hydrolysis of methyl DL-beta-acetylthioisobutyrate (DL-ester) to give D-beta-acetylthioisobutyric acid (DAT). To use the enzyme for DAT production, the esterase gene of Pseudomonas putida was cloned and expressed in E. coli. The recombinant E. coli containing the esterase gene produced a large amount of the enzyme in an active form. This strain could be used for the asymmetric synthesis of DAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…1996) and the synthesis of esters, as well as for the resolution of racemic mixtures (Margolin 1993). Enzymes with the specific esterase activity of hydrolysing (R)‐ or (S)‐carboxylic acid esters were identified from several Pseudomonas species, such as Pseudomonas fluorescens (Ozaki and Akihiro 1994), P. putida (Ozaki et al. 1994, 1995) and P. aeruginosa (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…1996) and the synthesis of esters, as well as for the resolution of racemic mixtures (Margolin 1993). Enzymes with the specific esterase activity of hydrolysing (R)‐ or (S)‐carboxylic acid esters were identified from several Pseudomonas species, such as Pseudomonas fluorescens (Ozaki and Akihiro 1994), P. putida (Ozaki et al. 1994, 1995) and P. aeruginosa (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are the esterases from Pseudomonas fluorescens (Choi, Jeohn, Rhee & Yoo, 1990;Hong, Jang, Choi & Yoo, 1991;Kim, Lee, Choi, Park & Yoo, 1994), P putida (Ozaki, Sakimae & Numazawa, 1994), and Pseudomonas sp. (McKay et al, 1992;Shimada et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A study of the hydrolytic reaction of methyl DL-␤-acetylthioisobutyrate (DL-MATI) with an esterase from Pseudomonas putida strain MR-2068 revealed that DAT had an optical purity of more than 98% when the reaction was done below pH 7.5 and below 50°C (34). Honda et al reported that 3,4-dihydrocoumarin hydrolase hydrolyzed DL-MATI to produce DAT with a high optical purity (Ͼ99.9% enantiomeric excess) (15).Esterases are widely distributed in Pseudomonas, and several have been identified, cloned, and sequenced, such as esterases of Pseudomonas fluorescens (6,7,16,20), Pseudomonas putida (27,28), and other Pseudomonas spp. (22,37,39,40).…”
mentioning
confidence: 99%
“…Esterases are widely distributed in Pseudomonas, and several have been identified, cloned, and sequenced, such as esterases of Pseudomonas fluorescens (6,7,16,20), Pseudomonas putida (27,28), and other Pseudomonas spp. (22,37,39,40).…”
mentioning
confidence: 99%